Trajetória e atuação política de Antônio de Souza Netto (1835-1866) - Silva, Matheus Luís da (2015)
This master thesis Trajectory and political action of Antônio de Souza Netto was developed in the Research Line Integration, Politics and Frontier , in the History Master s Degree in the Graduate School Program at Universidade Federal de Santa Maria, supported by CAPES/DS. The purpose of this master thesis was to investigate the trajectory and political action of the General Farroupilha Antônio de Souza Netto, mainly in the period after the Farroupilha Revolution (1835 1845). The general who proclaimed the Riograndense Republic was included in other conflicts in the La Plata Region and who served in these conflicts in accordance with the interests of the Empire. However, a part of the historiography argued in recente years that the Empire was forced to interfere in the region, in favor of the Brazilians who lived on the frontier of Rio Grande do Sul or beyond, to avoid a new attempt to separate the Province. In this sense, we demonstrate the political trajectory of Netto, a brazilian militar who lived in Uruguay. We seek to investigate the arguments used by the General to convince the Empire to answer the the demands of the Brazilians living in the Frontier. We did this work based in the political history and using as sources the newspapers, correspondences, Empire ministries reports, militar documentation, bibliographic, among others. The result of this research and crosschecking revealed an individual who has established strong relationships with various sectors of Imperial policy, with friends in the Parish and Court , solid built friendships and publicly defended. In this sense, we identified that the war, the land and the frontier are the foundation of his power and influence in the politics in the Empire in mid-nineteenth century, more precisely between the years 1845 to 1866, the year when the General Netto dies in the Paraguay War.